Female Inguinal Hernia – Conservatively Treated as Labial Swelling for a Long Time-A Case Report (BIRDEM Medical Journal, 2017)
Inguinal hernia in females is quite uncommon compared to males. However, in female it may pose both a diagnostic as well as surgical challenge to the attending surgeon. Awareness of anatomy of the region and all the possible contents is essential to prevent untoward complications. Here we are presenting a case of indirect inguinal hernia in a 25 years old women and how she was diagnosed and ultimately managed.Birdem Med J 2018; 8(1): 81-82